Prinsip Dasar Budha Zen dalam Chanoyu - Anastasia Merry Christiani Widya Putri; Ratna Handayani (Bina Nusantara University, 2010)
One of the Japanese traditional cultures that had been well known since the 16th century was chanoyu, the tea ceremony presented for the guests and carried out in chasitsu. Tea was introduced in Japan in the 16th century by bhiksu Zen. Formerly, the tea was used for a light stimulation for meditation, drug ingredients, media for Buddha Zen dissemination, dan developing chanoyu spiritual basic. One of the tea ceremony masters, Sen no Rikyu, used four basic principles in chanoyu, those were harmony (wa), respect (kei), purity (sei), silence (jaku). Article elaborated the four basic principles of Buddha Zen in tea ceremony applied in Urasenke chanoyu. Library research and descriptive analysis were applied in this research. The research results indicate that there are wa-keisei-jaku principles and wabi sabi concepts in the Japanese tea ceremony.